PROJECT-BASED LEARNING - LITERACY IN IMPROVING STUDENTS’ MATHEMATICAL REASONING ABILITIES IN ELEMENTARY SCHOOLS - Zaenal Abidin; Arif Cahyo Utomo; Vira Pratiwi; Laely Farokhah (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
The lower mathematical reasoning abilities of elementary school students are the background of this research. This happens because students have not been properly facilitated to develop the ability mathematical of reasoning. Mathematics learning can develop reasoning ability well because mathematics learning has systematic concepts and conceptual relationships. This will have an impact on logical, systematic and rational ways of thinking. Therefore, teachers must be able to choose learning models that can facilitate the ability of mathematical reasoning. One learning model that can be used is the literacy project-based learning model. This study aimed to determine the effectiveness of improving the ability of mathematical reasoning students who obtain literacy project-based learning. The design of this research was used pretest-posttest non-equivalent control group.  Based on research results, conclusions can be drawn about the effectiveness of learning that includes n-gain, minimum completeness criteria, and mastery learning. Literacy project-based learning has been effective in facilitating reasoning abilities. That is because literacy project-based learning can present contextual material with literacy works that are made and invited to carry out the process of thinking about the use of mathematical contexts in daily life. Furthermore, students can connect mathematical material with real-life contexts and can make reasoning to interpret learning well.